IMPLEMENTASI LAPORAN KEUANGAN METODE SAK EMKM DALAM PENGUATAN MANAJEMEN UMKM DI KABUPATEN KERINCI - Sestriyenti, Enny; Ariani, Fatma; Pajri, Mohd. (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This research was conducted to find out the problems of MSMEs related to the non-implementation of financial management in the form of a financial report with correct accounting concepts. financial statements with correct accounting concepts. Financial management in the form of form of financial statements with the SAK EMKM method which was actually prepared for simple financial reporting standards for micro, small and medium enterprises. medium, where in the end MSMEs can make financial reports as accountability and recommendations in decision making. and recommendations in decision making. The presence of SAK EMKM is to facilitate MSMEs in the transition of financial reporting from the concept of bookkeeping to financial statements on an actual basis. In the end, when an MSME has able to implement the preparation of financial reports using the SAK EMKM method, this can have a positive impact on the development of these MSMEs. With increasing the capacity of MSMEs in managing their management, then indirectly MSMEs will be able to play an important role in maintaining the sustainability and management of MSMEs. indirectly MSMEs will be able to play an important role in maintaining sustainability and supporting economic development in Indonesia. support economic development in Indonesia.